Premacular Cells as Source of Neurotrophic Factors in Idiopathic Macular Holes. (1st November 2020) - Vogt, Denise; Haritoglou, Christos; Mautone, Luca; Hagenau, Felix; Guenther, Stefanie R.; Wolf, Armin; Priglinger, Siegfried G.; Schumann, Ricarda G.
ABSTRACT: Purpose : To describe the presence of neurotrophic growth factors and histopathologic characteristics of internal limiting membrane (ILM) specimens obtained from large idiopathic full-thickness macular holes (FTMH). Methods : In 24 eyes of 24 patients with FTMH of diameter >400 µm, ILM specimens were harvested directly at the edge surrounding the macular hole during vitrectomy with peeling. We performed interference and phase contrast microscopy of flat mounts followed by immunostaining and transmission electron microscopy. Primary antigens directed against neurotrophic growth factors as well as antigens to glial and ganglion cells were used. Topographic relationship of cells and collagen was demonstrated by serial ultrathin sectioning. Results : Immunofluorescence microscopy demonstrated the presence of glial-derived neurotrophic factor and ciliary neurotrophic factor. Expression of vimentin, glial fibrillary acidic protein (GFAP), neurofilament, calretinin, and melanopsin was seen positive too. Cellular retinaldehyde-binding protein was seen positive in half of the specimens. Co-localisation of anti-GFAP as well as anti-vimentin with neurotrophic factors was found. Electron microscopy revealed cells exclusively on the vitreal side of the ILM. Cell fragments on the retinal side were rarely seen. Conclusion : In large FTMH, ILM specimens present positive immunolabelling of neurotrophic factors. The co-localization with macroglial cell markers suggests a premacular cell composition as a source of the neurotrophic factors. Ultrastructurally, premacular cells were found on the vitreal side of the ILM and not within the collagen network of the ILM itself.